The Impact of Side Friction on the Performance of Jalan D.I. Panjaitan in Sintang using the PKJI 2023 Method - Linnisa, Orva; Kadarini, S. Nurlaily; Mukti, Elsa Tri (Fakultas Teknik Universitas Tanjungpura, 2025)
Sintang Sub-district is the center of business, economic, and government activities in Sintang Regency, which leads to increased transportation needs. However, adequate infrastructure does not match this growth, resulting in traffic problems, especially side obstacles on Jalan D.I Panjaitan. This research aims to analyze the performance of Jalan D.I Panjaitan, evaluate the influence of side obstacles, and propose solutions to improve road performance. Data were analyzed using the Indonesian Road Capacity Manual (PKJI) 2023. The analysis results show that the level of side obstacles is in the Very High (VH) category. The degree of saturation on Saturday was 0,622, Sunday was 0,741, and Monday was 0,560. The road capacity is 957,168 SMP/hour with a free flow speed of 39,925 km/hour. The simulation of parking transfer to the sidewalk increases the road capacity to 1.123,632 SMP/hour and allows a free flow speed of 45,951 km/hour. The degree of saturation decreased to 0,530 on Saturday, 0,642 on Sunday, and 0,474 on Monday. Parking relocation is proven to increase road capacity, decrease the degree of saturation, and improve the level of service.